Adeninium cytosinium sulfate - Cherouana, Aouatef (International Union of Crystallography, 2009)
In the title compound, C(5)H(6)N(5) (+)·C(4)H(6)N(3)O(+)·SO(4) (2−), the adeninium (AdH(+)) and cytosinium (CytH(+)) cations and sulfate dianion are involved in a three-dimensional hydrogen-bonding network with four different modes, viz. AdH(+)⋯AdH(+), AdH(+)⋯CytH(+), AdH(+)⋯SO(4) (2−) and CytH(+)⋯SO(4) (2−). The adeninium cations form N—H⋯N dimers through the Hoogsteen faces, generating a characteristic R (2) (2)(10) motif. This AdH(+)⋯AdH(+) hydrogen bond in combination with AdH(+)⋯CytH(+ )H-bonds leads to two-dimensional cationic ribbons parallel to the a axis. The sulfate anions interlink the ribbons into a three-dimensional hydrogen-bonding network and thus reinforce the crystal structure.